2009
DOI: 10.1038/leu.2009.263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of acquired copy number alterations and uniparental disomies in cytogenetically normal acute myeloid leukemia using high-resolution single-nucleotide polymorphism analysis

Abstract: Recent advances in genome-wide single-nucleotide polymorphism (SNP) analyses have revealed previously unrecognized microdeletions and uniparental disomy (UPD) in a broad spectrum of human cancers. As acute myeloid leukemia (AML) represents a genetically heterogeneous disease, this technology might prove helpful, especially for cytogenetically normal AML (CN-AML) cases. Thus, we performed highresolution SNP analyses in 157 adult cases of CN-AML. Regions of acquired UPDs were identified in 12% of cases and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 47 publications
7
119
3
Order By: Relevance
“…These abnormalities include many gene mutations (NPM1 (nucleophosmin), FLT3 (fms-like tyrosine kinase receptor-3), CEBPA, MLL, N-RAS, RUNX1 (Runtrelated transcription factor 1), WT1 (Wilms tumor 1) and so on), 1 deregulation of gene expression (EVI1 (Ecotropic Viral Integration Site 1), BAALC (brain and acute leukemia, cytoplasmic), MN1 (meningioma 1), ERG (Ets-related gene), WT1 and so on), 2 --8 as well as acquired copy number variations and regions with loss of heterozygosity. 9,10 Prognostic significance within CN-AML has been well established for FLT3 internal tandem duplication (FLT3-ITD), NPM1 and CEBPA mutations. 11,12 NPM1 mutations confer a relatively favorable clinical outcome in CN-AML in the absence of a concomitant adverse FLT3-ITD.…”
Section: Introductionmentioning
confidence: 99%
“…These abnormalities include many gene mutations (NPM1 (nucleophosmin), FLT3 (fms-like tyrosine kinase receptor-3), CEBPA, MLL, N-RAS, RUNX1 (Runtrelated transcription factor 1), WT1 (Wilms tumor 1) and so on), 1 deregulation of gene expression (EVI1 (Ecotropic Viral Integration Site 1), BAALC (brain and acute leukemia, cytoplasmic), MN1 (meningioma 1), ERG (Ets-related gene), WT1 and so on), 2 --8 as well as acquired copy number variations and regions with loss of heterozygosity. 9,10 Prognostic significance within CN-AML has been well established for FLT3 internal tandem duplication (FLT3-ITD), NPM1 and CEBPA mutations. 11,12 NPM1 mutations confer a relatively favorable clinical outcome in CN-AML in the absence of a concomitant adverse FLT3-ITD.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest broad impacts of HLTF reduction on chromosomal instability across AML subtypes. Previous studies have shown that submicroscopic copy number alterations are present in about half of the cytogenetically normal AML patients, 35 and whether HLTF also impacts on these alterations warrants further investigation. Regarding prognostication, we revealed in this study an inverse correlation between reduced HLTF and CEBPA double mutations in adult AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent genome-wide single-nucleotide polymorphism analysis of 157 cytogenetically normal AML adult patients also reported a 17% aUPD incidence. 14 We report herein six patients whose HLA typing was performed on peripheral blood lymphocytes obtained from AML patients in acute phase at diagnosis and led to an apparent LOH as determined by PCR sequence-specific oligonucleotide (SSO)/ sequence-based typing (SBT) using locus-specific primers. Comparative genomic hybridization (CGH) on microarrays did not reveal any copy number variation of HLA loci at 6p21 that could account for the loss of haplotypes, and thus allowed to confirm that the HLA homozygosity was due to aUPD.…”
Section: Introductionmentioning
confidence: 99%